Operative production controlling as entrance into controlling 4.0 - Marcel Rolf Pfeifer (Trends Economics and Management, 2021)
Purpose of the article: The paper focuses on the potentials and benefits controlling provides for companies in the transition period towards industry 4.0. Operative production controlling provides data that shall be used in the future to apply the concept of smart factories. This article proposes a controlling archtitecture based on computer-aided standardization. Methodology/methods: The paper develops an architecture on operational production controlling based on an international literature review. Literature on controlling 4.0 are found mostly in publications in German language. While this literature has its focus on controlling as a whole or on strategic controlling, the paper has a look on operational controlling and its further usage and development towards smart factories. Scientific aim: The aim of this article is to develop a model of an operational production controlling architecture that is able to suite the requirements of smart factories by using computer-aided standarization. Findings: Research is working on concepts for industry 4.0 and its way towards real implementation. Competitive advantage in industry 4.0 is created through digitization and robotization. An architecture that fully complies to industry 4.0 is still waiting in real companies due to technical limitation in data storing, retrieval and processing as well as storage capacities. Conclusions: The paper discussed the devlopment of a controlling architecture suitable for industry 4.0. Already today controlling is making use of data. Smart factories shall make use of production data. Production controlling together with the CAS, that is able to provide standardized data on all manufacturing, maintenance, and auxiliary processes, systems are able to make a step forward towards smart factories. The concept of production controlling combined with the strengths of a CAS may be seen as the basis from which to target smart factories and industry 4.0.
Keywords: L11; L16; L60; M11; 650; production controlling; computer-aided standardisation; case; Industry 4.0; smart factories; machine-learning